2000
DOI: 10.1021/jp0015832
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Phenomena in the Mercury(II)−Chlorite Ion System:  Formation and Kinetic Role of the HgClO2+Complex

Abstract: On the basis of time-resolved spectrophotometric measurements, the formation of a novel chlorito complex, HgClO2 +, was confirmed under acidic condition in the mercury(II)−chlorite ion system. The complex formation occurs within the dead time of the stopped-flow instrument applied (τd ∼ 1 ms). The stability constant of HgClO2 + was determined from the initial part of the kinetic traces recorded at the characteristic 325 nm absorbance maximum of the complex:  K = 41.7 ± 1.9 M-1, ε325 = 727 ± 24 M-1 cm-1 (I = 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…When factors such as pH and temperature in the absorbing liquid changed, a series of decomposition reactions occurred. Based on the experimental results from Zhao et al’s and Fábián et al’s studies, 40 , 41 the ionic components in the NaClO/NaClO 2 solution were mainly ClO 3 – , ClO 2 – , ClO – , and Cl – . Under acidic conditions, the redox potentials of ClO – /Cl – , ClO 2 – /Cl – , and ClO 3 – /Cl – were 1.48, 1.57, and 1.45 V, respectively.…”
Section: Results and Discussionmentioning
confidence: 95%
“…When factors such as pH and temperature in the absorbing liquid changed, a series of decomposition reactions occurred. Based on the experimental results from Zhao et al’s and Fábián et al’s studies, 40 , 41 the ionic components in the NaClO/NaClO 2 solution were mainly ClO 3 – , ClO 2 – , ClO – , and Cl – . Under acidic conditions, the redox potentials of ClO – /Cl – , ClO 2 – /Cl – , and ClO 3 – /Cl – were 1.48, 1.57, and 1.45 V, respectively.…”
Section: Results and Discussionmentioning
confidence: 95%
“…This conclusion was confirmed in Figure 3. Fábián et al [15] reported that a novel chlorite complex HgClO 2 + played also an important role during the oxidation of Hg 0 . In order to further reveal the reaction mechanism, two parallel samples were taken from the bubble reactor, and the concentration of Hg 2+ in the spent absorption solution was determined.…”
Section: Mechanism Of Removal Of Hg 0 By Naclo 2 Solutionmentioning
confidence: 99%
“…By combining the discussions mentioned above and results of removal product analysis, and by referring to previous research results [15], the reaction mechanism for removing Hg 0 by acidic NaClO 2 solution was proposed as follows: 2 2 ClO H HClO …”
Section: Mechanism Of Removal Of Hg 0 By Naclo 2 Solutionmentioning
confidence: 99%
“…When the concentration of hydrogen ion (H + ) increased, the transient amount of ClO 2 decreased and the reactions become faster. Fábián et al [13] reported the formation of a novel chlorite complex, HgClO 2 + , and showed that this species played a significant role in the consumption of ClO 2 .…”
Section: Reaction Mechanismmentioning
confidence: 99%